Risk Factors Influencing Cognitive Function in Elderly Patients With Late‐Life Depression: A Scoping Review - Ping Jiang; Yunfeng Gao; Lin Wang; Xiaojun Shao; Lei Zhang; Gang Zhu; Li Duan (Brain and Behavior)
ABSTRACT Background In recent years, cognitive impairment has emerged as a pivotal symptom in elderly patients with depression, exerting a substantial impact on the course and prognosis of diseases. Moreover, it persists even following remission from depression during the rehabilitation period. However, there remains an incomplete understanding of the relevant influencing factors for cognitive impairment in elderly depressed patients, which seriously impedes the development of risk prediction models and the subsequent research on precision intervention programs. Objective The purpose of this study is to examine the current state of negative influencing factors and assessment tools for cognitive impairment in patients with late‐life depression (LLD), thereby providing a theoretical framework for the construction of subsequent targeted intervention programs. Methods The search strategy employed in this study followed an evidence‐based approach, utilizing a systematic scoping review to thoroughly explore six English and four Chinese databases up until November 2023. Two researchers independently conducted article screening and employed thematic analysis to categorize the results into themes. Results Following two rounds of rigorous screening conducted by the evidence‐based research team, data were meticulously extracted and succinctly summarized from five distinct themes encompassing socio‐demographic, physiological, psychological, genetic, and other related factors. In addition, a comprehensive compilation of 19 diverse assessment tools was undertaken. Ultimately, a total of 22 articles met the eligibility criteria for inclusion in this study. These comprised five longitudinal studies, nine pathological controlled studies, five cross‐sectional studies, two cohort studies, and one randomized controlled study. Conclusion Cognitive dysfunction is an important symptom of LLD, which seriously affects the survival of patients. At present, the research on its influencing factors mainly includes socio‐demographic, physiological, psychological, genetic, and other related factors. There have been existing cognitive function assessment tools specifically for those 18‐ to 65‐year‐old patients of major depressive disorder, but there is still a lack of reliability and validity tests in LLD.